Polymer / ionic liquid based gel electrolyte material and preparation method and application thereof
By using polymer/ionic liquid base gel electrolyte material in electro -changing devices, the problem of insufficient performance of electrolyte layer materials has been solved, and high -electric chemical performance and extremely high light transparency are realized. Essence
Patent Information
- Application Number
- CN202411802227.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-12-09
AI Technical Summary
In existing electrochromic devices, the material performance of the electrolyte layer is insufficient, which affects the overall performance and safety of the device. There are many challenges in both traditional liquid and solid electrolytes.
The polymer/ionic liquid base gel electrolyte material is used. The material modifies thermoplastic polymer through an imidazole -type ionic liquid to form a nano -fiber film that supports multi -stage structures, and interacts with alkaline metal salt electrolytes to enhance the interface ionic conductivity and Optical transparency.
It significantly improves the electrochemical performance and optical transparency of the electrolyte material, optimizes the color change and performance stability of the electrochromic device, and is suitable for the temperature range of -20°C to 60°C.
Smart Images

Figure CN119335787A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of electrolyte materials, and in particular to a polymer / ionic liquid based gel electrolyte material and a preparation method and application thereof. Background Art
[0002] Electrochromic technology is a phenomenon that regulates light and heat with low energy consumption and high efficiency under an applied voltage, and has broad application prospects in the fields of energy conservation and intelligence. Usually, an electrochromic device consists of five parts: a transparent conductive layer, an electrochromic layer, an electrolyte layer, an ion storage layer, and a transparent conductive layer. At present, in order to improve the overall performance of the device, most research focuses on the preparation and design of high-performance electrochromic layer materials, and less on the exploration and design of the electrolyte layer as a necessary channel for ion transmission. However, the electrolyte layer is not only responsible for conducting ions between electrodes, but also affects the safety and overall performance of the device. Therefore, improving the material properties of the electrolyte layer is of great significance for optimizing electrochromic devices and promoting the development of electrochromic energy-saving technology.
[0003] Generally speaking, an ideal electrolyte in an electrochromic device should have excellent mechanical, chemical and thermal stability, high optical transmittance, easy preparation, low cost and high voltage resistance. In addition, traditional liquid electrolytes have limitations in device applications such as easy leakage and difficult packaging. At the same time, solid electrolytes also face challenges such as unstable contact interface with electrodes, low ionic conductivity and high preparation cost. Therefore, the development of quasi-solid polymer electrolytes that are green, simple to prepare, and have the advantages of both liquid and solid electrolytes has become the key to solving these problems.
[0004] Polymer is a widely used material for polymer electrolyte substrates. The fully trans-polar phase with the maximum self-polarization in its molecular chain has excellent electrochemical properties and can enhance the charge transfer ability. However, in a single polymer, the non-polar phase is easily obtained by melt crystallization, while the polar phase is more difficult to form directly. Therefore, polymers still have limitations as electrolyte substrates. The current optimization methods include doping with inorganic or nanofillers, adding nucleating agents, using mechanical stretching to force molecular conformation, and electrospinning. Summary of the invention
[0005] The present invention aims to solve one of the technical problems in the related art to at least some extent. To this end, the present invention provides a polymer / ionic liquid-based gel electrolyte material and a preparation method and application thereof, wherein the method uses an imidazole-type ionic liquid to modify a thermoplastic polymer and forms a self-supporting multi-level nanofiber membrane through electrostatic action, and the polymer / ionic liquid nanofiber has a maximum all-trans polar conformation, and then interacts with an alkali metal salt electrolyte, thereby improving the interfacial ion conductivity while giving the electrolyte material extremely high optical transparency. The electrochromic device assembled from the prepared polymer / ionic liquid-based gel electrolyte material and the electrochromic electrode material shows excellent color changes and exhibits good performance at -20°C to 60°C.
[0006] To this end, the present invention provides a polymer / ionic liquid-based gel electrolyte material in a first aspect, wherein the polymer / ionic liquid-based gel electrolyte material comprises polymer / ionic liquid nanofibers and an alkali metal salt solution;
[0007] The polymer / ionic liquid nanofibers include a thermoplastic polymer whose surface is modified by an imidazole-type ionic liquid.
[0008] The polymer / ionic liquid-based gel electrolyte material provided by the present invention uses imidazole-type ionic liquid to modify and regulate the polymer microscopic molecular structure, which is beneficial to the ion transport and interface stability of the electrolyte material. The addition of alkali metal salt solution improves the interface ion conductivity while giving the electrolyte material extremely high optical transparency, significantly improving the electrochemical performance of the system.
[0009] According to an embodiment of the present invention, the alkali metal salt in the alkali metal salt solution includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium sulfate, sodium hexafluorophosphate, sodium bis(trifluoromethanesulfonyl)imide, potassium sulfate, and potassium hydroxide.
[0010] According to an embodiment of the present invention, the alkali metal salt solution further includes an ester organic solvent.
[0011] According to an embodiment of the present invention, the ester organic solvent includes at least one of ethyl acetate, methyl methacrylate, ethylene carbonate, propylene carbonate, diethyl carbonate, and triethyl phosphate.
[0012] According to an embodiment of the present invention, the content of the thermoplastic polymer in the polymer / ionic liquid nanofiber is 49.99wt%-99.99wt%, preferably 60wt%-90wt%.
[0013] According to an embodiment of the present invention, the content of the imidazolium-type ionic liquid is 0.01 wt%-50 wt%, preferably 1 wt%-20 wt%.
[0014] According to an embodiment of the present invention, the thermoplastic polymer includes at least one of polyacrylonitrile, polyvinyl alcohol, polymethyl methacrylate, polyacrylic acid or polyvinylidene fluoride-hexafluoropropylene.
[0015] According to an embodiment of the present invention, the imidazolium-type ionic liquid includes at least one of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
[0016] The second aspect of the present invention provides a method for preparing the polymer / ionic liquid-based gel electrolyte material according to the first aspect, comprising the following steps:
[0017] Preparation of polymer / ionic liquid nanofibers;
[0018] preparing an alkali metal salt solution;
[0019] The polymer / ionic liquid nanofibers are immersed in an alkali metal salt solution, taken out and allowed to stand to obtain the polymer / ionic liquid-based gel electrolyte material.
[0020] The invention obtains a polymer / ionic liquid-based gel electrolyte material through the preparation method. The material has good electrochemical performance and extremely high optical transparency.
[0021] According to an embodiment of the present invention, the immersion time is 1 min-120 min.
[0022] According to an embodiment of the present invention, every 1cm 2 The polymer / ionic liquid nanofibers are attached with 0.01 mL-1 mL of alkali metal salt solution.
[0023] According to an embodiment of the present invention, the concentration of the alkali metal salt solution is 0.01 mol / L-50 mol / L.
[0024] According to an embodiment of the present invention, the preparation process of the polymer / ionic liquid nanofibers includes:
[0025] A mixed solution containing a thermoplastic polymer and an imidazole-type ionic liquid is prepared, and a polymer / ionic liquid nanofiber precursor is obtained by electrospinning;
[0026] The polymer / ionic liquid nanofiber precursor is annealed to obtain the polymer / ionic liquid nanofiber.
[0027] According to an embodiment of the present invention, the voltage of the electrospinning is 5 kV-25 kV, the flow rate is 0.01 mL / h-20 mL / h, and the collection distance is 10 cm-30 cm.
[0028] According to an embodiment of the present invention, the annealing temperature is 50° C.-200° C., and the annealing time is 6 h-24 h.
[0029] The third aspect of the present invention provides an application of the polymer / ionic liquid-based gel electrolyte material described in the first aspect or the polymer / ionic liquid-based gel electrolyte material obtained according to the preparation method described in the second aspect in an electrochromic device.
[0030] The polymer / ionic liquid-based gel electrolyte material proposed in the present invention has low main raw materials, simple preparation process, easy control, and high practical cost performance. The material is combined with an electrode material having electrochromic properties to form a sandwich-structured electrochromic device, which significantly improves the visible light modulation capability of the device, accelerates the response speed, and prolongs the cycle life.
[0031] According to an embodiment of the present invention, the polymer / ionic liquid-based gel electrolyte material is used to combine with an electrochromic electrode material to assemble an electrochromic device.
[0032] According to an embodiment of the present invention, the electrochromic electrode material includes an inorganic material and / or an organic material.
[0033] According to an embodiment of the present invention, the inorganic material includes at least one of manganese dioxide, tungsten trioxide or Prussian blue.
[0034] According to an embodiment of the present invention, the organic material includes at least one of polypyrrole, polyaniline or polythiophene.
[0035] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0037] Figure 1 The X-ray diffraction spectrum of the polymer / ionic liquid nanofiber prepared in Example 1 of the present invention is shown;
[0038] Figure 2 A scanning electron microscope image of the polymer / ionic liquid-based gel electrolyte material prepared in Example 1 of the present invention is shown;
[0039] Figure 3The visible light band transmission spectrum and optical photograph of the polymer / ionic liquid-based gel electrolyte material prepared in Example 1 of the present invention are shown. Among them, Figure a is a visible light band transmission spectrum; Figure b is an optical photograph;
[0040] Figure 4 The ionic conductivity-temperature curve of the polymer / ionic liquid-based gel electrolyte material prepared in Example 1 of the present invention is shown;
[0041] Figure 5 The optical photographs of the color change effect of the device at different voltages, the transmission spectrum of the visible light band, the transmittance and time curves, and the characterization of the cycle stability of the device in the voltage range of -2V to 2V are shown when the polymer / ionic liquid-based gel electrolyte material prepared in Example 1 of the present invention is assembled into an electrochromic device with Prussian blue and tungsten trioxide as the positive and negative electrodes. Among them, Figure a is an optical photograph of the color change effect of the electrochromic device at different voltages; Figure b is a transmission spectrum of the visible light band; Figure c is a transmittance and time curve; Figure d is a characterization of the cycle stability of the electrochromic device in the voltage range of -2V to 2V. DETAILED DESCRIPTION
[0042] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.
[0043] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.
[0044] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0045] In order to make the present invention more easily understood, certain technical and scientific terms are specifically defined below. Unless otherwise clearly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.
[0046] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.
[0047] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.
[0048] According to an embodiment of the present invention, a first aspect of the present invention provides a polymer / ionic liquid based gel electrolyte material, wherein the polymer / ionic liquid based gel electrolyte material comprises polymer / ionic liquid nanofibers and an alkali metal salt solution;
[0049] The polymer / ionic liquid nanofibers include a thermoplastic polymer whose surface is modified by an imidazole-type ionic liquid.
[0050] The present invention uses imidazole-type ionic liquids to modify and regulate the microscopic molecular structure of thermoplastic polymers, which is beneficial to the ion transport and interface stability of electrolyte materials, and forms a self-supporting multi-level nanofiber membrane through electrostatic action. The polymer / ionic liquid nanofibers have a maximum all-trans polar conformation, and then interact with the alkali metal salt electrolyte. On the one hand, it improves the movement of polymer segments, accelerates the dissociation rate of alkali metal ions, and enhances the interface ion conductivity; on the other hand, the large specific surface area and three-dimensional network structure of the nanofibers increase the filling volume of the electrolyte, giving the electrolyte material extremely high optical transparency, so that the polymer / ionic liquid-based gel electrolyte material obtained by the present invention has more excellent performance.
[0051] According to a specific embodiment of the present invention, the type of alkali metal salt in the alkali metal salt solution is not particularly limited. As some specific examples, the alkali metal salt includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium sulfate, sodium hexafluorophosphate, sodium bis(trifluoromethanesulfonyl)imide, potassium sulfate, and potassium hydroxide.
[0052] According to a specific embodiment of the present invention, the alkali metal salt solution further comprises an ester organic solvent. The type of the ester organic solvent is not particularly limited. As some specific examples, the ester organic solvent comprises at least one of ethyl acetate, methyl methacrylate, ethylene carbonate, propylene carbonate, diethyl carbonate, and triethyl phosphate.
[0053] According to a specific embodiment of the present invention, the content of the thermoplastic polymer in the polymer / ionic liquid nanofiber is 49.99wt%-99.99wt%, preferably 60wt%-90wt%. As some specific examples, the content of the thermoplastic polymer may be 49.99wt%, 50wt%, 60wt%, 70wt%, 80wt%, 90wt%, 99.99wt%, etc.
[0054] According to a specific embodiment of the present invention, the content of the imidazolium-type ionic liquid is 0.01wt%-50wt%, preferably 1wt%-20wt%. As some specific examples, the content of the imidazolium-type ionic liquid may be 0.01wt%, 0.05wt%, 0.1wt%, 0.5wt%, 1wt%, 5wt%, 10wt%, 20wt%, 30wt%, 40wt%, 50wt% and the like.
[0055] According to a specific embodiment of the present invention, the type of the thermoplastic polymer is not particularly limited. As some specific examples, the thermoplastic polymer includes at least one of polyacrylonitrile, polyvinyl alcohol, polymethyl methacrylate, polyacrylic acid or polyvinylidene fluoride-hexafluoropropylene.
[0056] According to a specific embodiment of the present invention, the type of the imidazolium-type ionic liquid is not particularly limited. As some specific examples, the imidazolium-type ionic liquid includes at least one of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
[0057] According to a specific embodiment of the present invention, the diameter of the polymer / ionic liquid nanofiber is 10nm-5000nm. As some specific examples, the diameter of the polymer / ionic liquid nanofiber can be 10nm, 50nm, 100nm, 500nm, 1000nm, 2000nm, 3000nm, 4000nm, 5000nm, etc. The polymer / ionic liquid nanofiber thus obtained has a suitable porosity and can carry a certain mass of electrolyte to exert the excellent electrochemical properties of the quasi-solid electrolyte.
[0058] According to a specific embodiment of the present invention, the length of the polymer / ionic liquid nanofiber is 1 μm-2000 μm. As some specific examples, the length of the polymer / ionic liquid nanofiber can be 1 μm, 5 μm, 10 μm, 50 μm, 100 μm, 500 μm, 1000 μm, 2000 μm, etc. Thus, continuous nanofibers are obtained, which have strong mechanical robustness and can be used as an electrolyte skeleton with self-supporting ability.
[0059] According to a specific embodiment of the present invention, the material thickness of the polymer / ionic liquid nanofiber is 0.01mm-50mm. The longer the electrospinning time is, the thicker the accumulated fiber film is. The thickness determines the overall thickness of the electrolyte and the distance between the two electrode materials in the electrochromic device. As some specific examples, the material thickness of the polymer / ionic liquid nanofiber can be 0.01mm, 0.05mm, 0.1mm, 0.5mm, 1mm, 5mm, 10mm, 20mm, 30mm, 40mm, 50mm, etc. The polymer / ionic liquid nanofiber thus obtained has a suitable porosity and can carry a certain mass of electrolyte to exert the excellent electrochemical properties of the quasi-solid electrolyte.
[0060] According to an embodiment of the present invention, the second aspect of the present invention provides a method for preparing the polymer / ionic liquid-based gel electrolyte material according to the first aspect, comprising the following steps:
[0061] (1) Preparation of polymer / ionic liquid nanofibers.
[0062] According to a specific embodiment of the present invention, the preparation method of the polymer / ionic liquid nanofibers is not particularly limited, and is preferably obtained by electrospinning, and the specific process includes:
[0063] A. preparing a mixed solution containing a thermoplastic polymer and an imidazole-type ionic liquid, and obtaining a polymer / ionic liquid nanofiber precursor by electrospinning;
[0064] According to a specific embodiment of the present invention, the voltage of the electrospinning is 5kV-25kV, the flow rate is 0.01mL / h-20mL / h, and the collection distance is 10cm-30cm. As some specific examples, the voltage of the electrospinning may be 5kV, 10kV, 15kV, 20kV, 25kV, etc., the flow rate may be 0.01mL / h, 0.05mL / h, 0.1mL / h, 0.5mL / h, 1mL / h, 5mL / h, 10mL / h, 15mL / h, 20mL / h, etc., and the collection distance may be 10cm, 20cm, 30cm, etc.
[0065] According to a specific embodiment of the present invention, the mixed solution also includes a solvent, and the type of the solvent is not particularly limited. As some specific examples, the solvent includes at least one of water, anhydrous ethanol, anhydrous methanol, acetone, ethylene glycol, and dimethylformamide.
[0066] B. Annealing the polymer / ionic liquid nanofiber precursor to obtain the polymer / ionic liquid nanofiber.
[0067] According to a specific embodiment of the present invention, the annealing temperature is 50°C-200°C, and the time is 6h-24h. As some specific examples, the annealing temperature may be 50°C, 100°C, 150°C, 200°C, etc., and the time may be 6h, 12h, 18h, 24h, etc.
[0068] (2) Prepare alkali metal salt solution.
[0069] According to a specific embodiment of the present invention, the concentration of the alkali metal salt solution is not particularly limited. As some specific examples, the concentration of the alkali metal salt solution is 0.01mol / L-50mol / L, specifically 0.01mol / L, 0.05mol / L, 0.1mol / L, 0.5mol / L, 1mol / L, 5mol / L, 10mol / L, 20mol / L, 30mol / L, 40mol / L, 50mol / L, etc.
[0070] (3) Immersing the polymer / ionic liquid nanofibers in an alkali metal salt solution, taking them out and letting them stand, thereby obtaining the polymer / ionic liquid-based gel electrolyte material.
[0071] The addition of alkali metal salt solution not only improves the interfacial ionic conductivity but also gives the electrolyte material extremely high optical transparency, significantly improving the electrochemical performance of the system.
[0072] According to a specific embodiment of the present invention, the immersion time is 1 min-120 min. As some specific examples, the immersion time may be 1 min, 5 min, 10 min, 20 min, 40 min, 60 min, 80 min, 100 min, 120 min, etc.
[0073] According to a specific embodiment of the present invention, every 1cm 2 The polymer / ionic liquid nanofibers are attached with 0.01mL-1mL of alkali metal salt solution. This amount of attachment is the most suitable amount for preparing the electrolyte. It will not be squeezed out of the fiber frame and will not cause the electrolyte surface to be uneven. As some specific examples, every 1cm 2 The polymer / ionic liquid nanofibers can be attached with 0.01 mL, 0.05 mL, 0.1 mL, 0.2 mL, 0.4 mL, 0.6 mL, 0.8 mL, and 1 mL of the alkali metal salt solution.
[0074] According to a specific embodiment of the present invention, in this step, the alkali metal salt solution may be contacted with the polymer / ionic liquid nanofibers by drop coating, without affecting the performance of the obtained material.
[0075] According to an embodiment of the present invention, the third aspect of the present invention provides an application of the polymer / ionic liquid-based gel electrolyte material described in the first aspect or the polymer / ionic liquid-based gel electrolyte material obtained according to the preparation method described in the second aspect in an electrochromic device.
[0076] The polymer / ionic liquid-based gel electrolyte material proposed in the present invention has low main raw materials, simple preparation process, easy control, and high practical cost performance. The material is combined with an electrode material having electrochromic properties to form a sandwich-structured electrochromic device, which significantly improves the visible light modulation capability of the device, accelerates the response speed, and prolongs the cycle life.
[0077] According to a specific embodiment of the present invention, the polymer / ionic liquid-based gel electrolyte material is used to combine with an electrochromic electrode material to assemble an electrochromic device.
[0078] According to a specific embodiment of the present invention, the electrochromic electrode material includes inorganic material and / or organic material.
[0079] According to a specific embodiment of the present invention, the type of the inorganic material is not particularly limited. As some specific examples, the inorganic material includes at least one of manganese dioxide, tungsten trioxide or Prussian blue.
[0080] According to a specific embodiment of the present invention, the type of the organic material is not particularly limited. As some specific examples, the organic material includes at least one of polypyrrole, polyaniline or polythiophene.
[0081] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.
[0082] Example 1
[0083] (1) 2.0 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) powder was dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and acetone (50:50, volume ratio), and stirred at 50 °C for 6 h to obtain a transparent polymer solution;
[0084] (2) dispersing 1 g of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid (BmImTFSI) into the polymer solution and stirring at room temperature to obtain a PVDF-HFP / BmImTFSI electrospinning precursor solution;
[0085] (3) The PVDF-HFP / BmImTFSI electrospinning precursor solution was sucked into a plastic syringe equipped with a 20G stainless steel needle, and electrospinning was performed under the conditions of a syringe injection speed of 1 mL / h, a collection distance of 25 cm, and a DC voltage of 15 kV;
[0086] (4) annealing the obtained PVDF-HFP / BmImTFSI polymer / ionic liquid nanofiber precursor in a vacuum drying oven at 120° C. for 12 h to obtain PVDF-HFP / BmImTFSI polymer / ionic liquid nanofibers;
[0087] (5) Weigh a certain amount of lithium bis(trifluoromethanesulfonyl)imide and dissolve it in propylene carbonate to make the total concentration of lithium salt 1M / L. After mixing evenly, PVDF-HFP / BmImTFSI polymer / ionic liquid nanofibers are immersed for 1 min, taken out and allowed to stand, to obtain a uniform and transparent PVDF-HFP / BmImTFSI polymer / ionic liquid-based gel electrolyte material.
[0088] The electrochromic device is prepared by conventional assembly means in the art: PVDF-HFP / BmImTFSI polymer / ionic liquid-based gel electrolyte material is connected with ITO or FTO glass with Prussian blue and tungsten trioxide through an adhesive to form an electrochromic device with a sandwich structure.
[0089] The X-ray diffraction spectrum of the polymer / ionic liquid nanofibers obtained according to the above preparation method is as follows: Figure 1 As shown, the scanning electron microscopy image of the polymer / ionic liquid based gel electrolyte material is as follows Figure 2 As shown in the figure, the visible light transmission spectrum of the polymer / ionic liquid based gel electrolyte material and its optical photograph are as follows Figure 3 As shown in Figure 2, the ionic conductivity-temperature curve of polymer / ionic liquid based gel electrolyte materials is as follows: Figure 4 As shown in the figure, the optical photos of the color change effect of the electrochromic device at different voltages, the transmission spectrum of the visible light band, the transmittance and time curve, and the characterization of the cyclic stability of the device in the voltage range of -2V to 2V are shown in the figure. Figure 5 shown.
[0090] Example 2
[0091] (1) 5 mL of polymethyl methacrylate (PMMA) solution was dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and acetone (50:50, volume ratio), and stirred at room temperature for 2 h to obtain a transparent polymer solution;
[0092] (2) dispersing 1 g of 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid (EmImTFSI) into the polymer solution and stirring at room temperature to obtain a PMMA / EmImTFSI electrospinning precursor solution;
[0093] (3) The PMMA / EmImTFSI electrospinning precursor solution was sucked into a plastic syringe equipped with a 20G stainless steel needle, and electrospinning was performed under the conditions of a syringe injection speed of 1 mL / h, a collection distance of 25 cm, and a 10 kV DC voltage;
[0094] (4) annealing the obtained PMMA / EmImTFSI polymer / ionic liquid nanofiber precursor in a vacuum drying oven at 120° C. for 12 h to obtain PMMA / EmImTFSI polymer / ionic liquid nanofibers;
[0095] (5) Weigh a certain amount of lithium bis(trifluoromethanesulfonyl)imide and dissolve it in propylene carbonate to make the total concentration of lithium salt 1M / L. After mixing evenly, immerse PMMA / EmImTFSI polymer / ionic liquid nanofibers for 1 min, take them out and let them stand, and obtain a uniform and transparent PMMA / EmImTFSI polymer / ionic liquid-based gel electrolyte material.
[0096] Example 3
[0097] (1) 5 g of polyacrylic acid (PAA) powder was dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and acetone (50:50, volume ratio), and stirred at 100 °C for 6 h to obtain a transparent polymer solution;
[0098] (2) dispersing 1 g of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid (EmImTFSI) into the polymer solution and stirring at room temperature to obtain a PAA / EmImTFSI electrospinning precursor solution;
[0099] (3) The PAA / EmImTFSI electrospinning precursor solution was sucked into a plastic syringe equipped with a 20G stainless steel needle, and electrospinning was performed under the conditions of a syringe injection speed of 1 mL / h, a collection distance of 25 cm, and a 10 kV DC voltage;
[0100] (4) annealing the obtained PAA / EmImTFSI polymer / ionic liquid nanofiber precursor in a vacuum drying oven at 120° C. for 12 h to obtain PAA / EmImTFSI polymer / ionic liquid nanofibers;
[0101] (5) Weigh a certain amount of lithium bis(trifluoromethanesulfonyl)imide and dissolve it in propylene carbonate to make the total concentration of lithium salt 1M / L. After mixing evenly, immerse the PAA / EmImTFSI polymer / ionic liquid nanofibers for 1 min, take them out and let them stand, and obtain a uniform and transparent PAA / EmImTFSI polymer / ionic liquid-based gel electrolyte material.
[0102] Example 4
[0103] (1) 2.0 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) powder was dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and acetone (5:5, volume ratio), and stirred at 50 °C for 6 h to obtain a transparent polymer solution;
[0104] (2) dispersing 1 g of 1-butyl-3-methylimidazolium tetrafluoroborate ionic liquid (BmImBF4) into the polymer solution and stirring at room temperature to obtain a PVDF-HFP / BmImBF4 electrospinning precursor solution;
[0105] (3) The PVDF-HFP / BmImBF4 electrospinning precursor solution was sucked into a plastic syringe equipped with a 20G stainless steel needle, and electrospinning was performed under the conditions of a syringe injection speed of 1 mL / h, a collection distance of 25 cm, and a DC voltage of 20 kV;
[0106] (4) annealing the obtained PVDF-HFP / BmImBF4 polymer / ionic liquid nanofiber precursor in a vacuum drying oven at 120° C. for 12 h to obtain PVDF-HFP / BmImBF4 polymer / ionic liquid nanofiber;
[0107] (5) Weigh a certain amount of lithium bis(trifluoromethanesulfonyl)imide and dissolve it in propylene carbonate to make the total concentration of lithium salt 1M / L. After mixing evenly, PVDF-HFP / BmImBF4 polymer / ionic liquid nanofibers are immersed for 1 min, taken out and allowed to stand, to obtain a uniform and transparent PVDF-HFP / BmImBF4 polymer / ionic liquid-based gel electrolyte material.
[0108] Example 5
[0109] (1) 2.0 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) powder was dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and acetone (5:5, volume ratio), and stirred at 50 °C for 6 h to obtain a transparent polymer solution;
[0110] (2) dispersing 0.5 g of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid (BmImTFSI) into the polymer solution and stirring at room temperature to obtain a PVDF-HFP / BmImTFSI electrospinning precursor solution;
[0111] (3) The PVDF-HFP / BmImTFSI electrospinning precursor solution was sucked into a plastic syringe equipped with a 20G stainless steel needle, and electrospinning was performed under the conditions of a syringe injection speed of 1 mL / h, a collection distance of 25 cm, and a DC voltage of 15 kV;
[0112] (4) annealing the obtained PVDF-HFP / BmImTFSI polymer / ionic liquid nanofiber precursor in a vacuum drying oven at 150° C. for 12 h to obtain PVDF-HFP / BmImTFSI polymer / ionic liquid nanofibers;
[0113] (5) Weigh a certain amount of lithium bis(trifluoromethanesulfonyl)imide and dissolve it in propylene carbonate to make the total concentration of lithium salt 1M / L. After mixing evenly, PVDF-HFP / BmImTFSI polymer / ionic liquid nanofibers are immersed for 1 min, taken out and allowed to stand, to obtain a uniform and transparent PVDF-HFP / BmImTFSI polymer / ionic liquid-based gel electrolyte material.
[0114] Example 6
[0115] (1) 2.0 g of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) powder was dissolved in 10 mL of a mixed solvent of N,N-dimethylformamide and acetone (5:5, volume ratio), and stirred at 50 °C for 6 h to obtain a transparent polymer solution;
[0116] (2) dispersing 0.5 g of 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid (BmImTFSI) into the polymer solution and stirring at room temperature to obtain a PVDF-HFP / BmImTFSI electrospinning precursor solution;
[0117] (3) The PVDF-HFP / BmImTFSI electrospinning precursor solution was sucked into a plastic syringe equipped with a 20G stainless steel needle, and electrospinning was performed under the conditions of a syringe injection speed of 1 mL / h, a collection distance of 25 cm, and a DC voltage of 15 kV;
[0118] (4) annealing the obtained PVDF-HFP / BmImTFSI polymer / ionic liquid nanofiber precursor in a vacuum drying oven at 120° C. for 12 h to obtain PVDF-HFP / BmImTFSI polymer / ionic liquid nanofibers;
[0119] (5) Weigh a certain amount of lithium bis(trifluoromethanesulfonyl)imide and dissolve it in triethyl phosphate to make the total concentration of sodium salt 2M / L. After mixing evenly, slowly drop it onto the PVDF-HFP / BmImTFSI polymer / ionic liquid nanofibers to obtain a uniform and transparent PVDF-HFP / BmImTFSI polymer / ionic liquid-based gel electrolyte material.
[0120] Comparative Example 1
[0121] The difference between this comparative example and Example 1 is that the type of polymer selected in step (1) is polyurethane (PU), the content of the polymer in the polymer / ionic liquid nanofibers is 80wt%, and the type of mixed ionic liquid is 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid (EmImTFSI).
[0122] The results show that the obtained electrospun material has poor mechanical properties, and the microstructure contains nanofibers with beaded structures, and the expected structure cannot be obtained; it cannot carry the same mass of electrolyte as in Example 1, and the electrochemical performance is poor. Therefore, the performance of Comparative Example 1 does not reach the effect of the present invention.
[0123] Comparative Example 2
[0124] The difference between this comparative example and Example 1 is that the type of polymer selected in step (1) is polyethylene oxide (PEO), the content of the polymer in the polymer / ionic liquid nanofibers is 80wt%, and the type of mixed ionic liquid is 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide ionic liquid (EmImTFSI).
[0125] The results show that the obtained polymer / ionic liquid-based gel electrolyte material has low optical transmittance and large haze. Therefore, the visible light modulation capability of the assembled electrochromic device is reduced, and the effect of the present invention cannot be achieved.
[0126] Comparative Example 3
[0127] The only difference between this comparative example and Example 1 is that the ionic liquid selected in step (2) is replaced with butylpyridinium boron tetrafluoride, and the content of the ionic liquid in the polymer / ionic liquid nanofibers is 10 wt%.
[0128] The results showed that: the electrospinning needle was easily clogged, nanofibers were difficult to form, and the formed fibers were short clustered rod-shaped fibers with a length of less than 1 μm; and after the material was annealed, the nanofibers were easily broken and difficult to separate from the aluminum foil; therefore, the electrochemical performance achieved by the present invention could not be achieved.
[0129] Comparative Example 4
[0130] The difference between this comparative example and Example 1 is only that step (5) is omitted.
[0131] The results show that the obtained polymer / ionic liquid based gel electrolyte material has low optical transmittance, slow ion transmission rate and large electrolyte internal impedance. Therefore, the assembled electrochromic device has slow color fading response time and low visible light modulation capability, and fails to achieve the effect of the present invention.
[0132] Comparative Example 5
[0133] The only difference between this comparative example and Example 1 is that the metal salt solution in step (5) is replaced with zinc sulfate / triethyl phosphate, and the concentration is 2 M / L.
[0134] The results show that the obtained polymer / ionic liquid-based gel electrolyte material has white crystals precipitated when exposed to air for a long time at room temperature. Therefore, the stability cannot be guaranteed and the effect of the present invention cannot be achieved.
[0135] Depend on Figure 1 It can be seen that the content of all-trans polar β phase in the crystalline region of the PVDF-HFP nanofibers modified with BmImTFSI in Example 1 of the present invention is much greater than that of the pure polymer nanofibers without BmImTFSI, which proves the induced polarization effect of BmImTFSI on the polymer; Figure 2 It can be seen that the PVDF-HFP / BmImTFSI polymer / ionic liquid-based gel electrolyte material was successfully prepared, showing the multi-level structure of PVDF-HFP / BmImTFSI polymer / ionic liquid nanofibers immersed in lithium salt solution, in which the diameter of the nanofibers after being infiltrated with the electrolyte was about 150nm and the length was about 100μm; Figure 3 It can be seen that the PVDF-HFP / BmImTFSI polymer / ionic liquid-based gel electrolyte material in this application has extremely high optical transmittance ( Figure 3 a), and higher than pure PVDF-HFP nanofiber electrolyte material, indicating that the electrolyte sample will not interfere with the fading effect of the electrochromic electrode in the device ( Figure 3 b), can be applied to the field of electrochromic energy-saving windows; Figure 4 It can be seen that the PVDF-HFP / BmImTFSI polymer / ionic liquid-based gel electrolyte material in the present application has an excellent ion migration rate, proving that it has good ionic conductivity at low temperature, room temperature and high temperature, among which it has better electrochemical performance at high temperature; Figure 5 It can be seen that the PVDF-HFP / BmImTFSI polymer / ionic liquid-based gel electrolyte material in this application is combined with tungsten trioxide and Prussian blue as the electrochromic material layer of the anode and cathode to assemble into a Prussian blue||PVDF-HFP / BmImTFSI polymer / ionic liquid-based gel electrolyte material||tungsten trioxide electrochromic device; Figure 5 a, when -2.5V voltage is applied, the device shows a blue-black coloring state, when 0V voltage is applied, the device shows a light blue coloring state, and when 2.5V voltage is applied, the device shows a faded state of almost transparent color; Figure 5 b and 5c, when switching between -2.5 V and 2.5 V, the device using PVDF-HFP / BmImTFSI polymer / ionic liquid-based gel electrolyte material shows a more excellent color-changing performance with modulation capability; and, as Figure 5 d, When switching voltages of -2 V and 2 V were applied, the device using PVDF-HFP / BmImTFSI polymer / ionic liquid-based gel electrolyte material also exhibited better cycling stability.
[0136] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0137] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.
Claims
1. A polymer / ionic liquid based gel electrolyte material, characterized in that: The polymer / ionic liquid based gel electrolyte material comprises polymer / ionic liquid nanofibers and an alkali metal salt solution; The polymer / ionic liquid nanofibers include a thermoplastic polymer whose surface is modified by an imidazole-type ionic liquid.
2. The polymer / ionic liquid based gel electrolyte material according to claim 1, characterized in that: The alkali metal salt in the alkali metal salt solution includes at least one of lithium hexafluorophosphate, lithium bis(trifluoromethanesulfonyl)imide, lithium sulfate, sodium hexafluorophosphate, sodium bis(trifluoromethanesulfonyl)imide, potassium sulfate, and potassium hydroxide; Optionally, the alkali metal salt solution further comprises an ester organic solvent; Optionally, the ester organic solvent includes at least one of ethyl acetate, methyl methacrylate, ethylene carbonate, propylene carbonate, diethyl carbonate, and triethyl phosphate.
3. The polymer / ionic liquid based gel electrolyte material according to claim 1, characterized in that: The content of the thermoplastic polymer in the polymer / ionic liquid nanofiber is 49.99wt%-99.99wt%, preferably 60wt%-90wt%; Optionally, the content of the imidazolium-type ionic liquid is 0.01 wt%-50 wt%, preferably 1 wt%-20 wt%.
4. The polymer / ionic liquid based gel electrolyte material according to claim 1, characterized in that: The thermoplastic polymer includes at least one of polyacrylonitrile, polyvinyl alcohol, polymethyl methacrylate, polyacrylic acid or polyvinylidene fluoride-hexafluoropropylene; Optionally, the imidazolium-type ionic liquid includes at least one of 1-ethyl-3-methylimidazolium tetrafluoroborate, 1-butyl-3-methylimidazolium tetrafluoroborate, 1-ethyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide, and 1-butyl-3-methylimidazolium bis(trifluoromethanesulfonyl)imide.
5. A method for preparing the polymer / ionic liquid based gel electrolyte material according to any one of claims 1 to 4, characterized in that: The following steps are involved: Preparation of polymer / ionic liquid nanofibers; preparing an alkali metal salt solution; The polymer / ionic liquid nanofibers are immersed in an alkali metal salt solution, taken out and allowed to stand to obtain the polymer / ionic liquid-based gel electrolyte material.
6. The preparation method according to claim 5, characterized in that: The immersion time is 1 min-120 min; Optionally, every 1 cm 2 The polymer / ionic liquid nanofibers are attached with 0.01 mL-1 mL of alkali metal salt solution; Optionally, the concentration of the alkali metal salt solution is 0.01 mol / L-50 mol / L.
7. The preparation method according to claim 5, characterized in that: The preparation process of the polymer / ionic liquid nanofiber comprises: A mixed solution containing a thermoplastic polymer and an imidazole-type ionic liquid is prepared, and a polymer / ionic liquid nanofiber precursor is obtained by electrospinning; The polymer / ionic liquid nanofiber precursor is annealed to obtain the polymer / ionic liquid nanofiber.
8. The preparation method according to claim 7, characterized in that: The voltage of the electrospinning is 5 kV-25 kV, the flow rate is 0.01 mL / h-20 mL / h, and the collection distance is 10 cm-30 cm; Optionally, the annealing temperature is 50° C.-200° C., and the annealing time is 6 h-24 h.
9. Use of the polymer / ionic liquid-based gel electrolyte material according to any one of claims 1 to 4 or the polymer / ionic liquid-based gel electrolyte material obtained by the preparation method according to any one of claims 5 to 8 in an electrochromic device.
10. The use according to claim 9, characterized in that: The polymer / ionic liquid-based gel electrolyte material is used to combine with an electrochromic electrode material to assemble an electrochromic device; Optionally, the electrochromic electrode material comprises an inorganic material and / or an organic material; Optionally, the inorganic material includes at least one of manganese dioxide, tungsten trioxide or Prussian blue; Optionally, the organic material includes at least one of polypyrrole, polyaniline or polythiophene.
Citation Information
Patent Citations
Porous polymer electrolyte supporting membrane material, preparation method thereof and application thereof
CN102199846A
Solid electrolyte and preparation method thereof and lithium ion battery
CN111900468A
Composite quasi-solid-state electrolyte film, preparation method thereof and application of composite quasi-solid-state electrolyte film in solid-state lithium battery
CN117895070A
Gel polymer electrolyte containing ionic liquid and electrochromic device using the same
CN1934212A
Cited By
Flexible fibrous infrared emissivity regulation and control device and preparation method thereof
CN122218991A